Petroleum operations in Nigeria - Oremade, Tunde (Lagos, Nigeria : West African Book Publishers, 1986)
This book explains the operations and procedures of the oil industry in Nigeria
asm: 21/01/19
Loans
Keywords: Petroleum industry and trade